1985
DOI: 10.1007/bf02148892
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of flow-physiologic parameters of retinal blood circulation in type 1 and 2 diabetics before and after photocoagulation

Abstract: In seven diabetics of type 1 and seven of type 2, the flow physiologic magnitudes were measured in a retinal quadrant before and after photocoagulation. The segmental blood flow, the arterial flow velocity, and the diameters of artery and vein are smaller after photocoagulation than before. Investigations into the time course of the flow-physiologic parameters following photocoagulation show that the flow-physiologic values are stationary about 2 weeks after photocoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…The results, however, have been somewhat contradictory: Compared to healthy control groups, elevated [17,18,28,36], reduced [4][5][6], or unchanged [13,15,16,20] flow values were found in diabetics with no or non-proliferative retinopathy. In proliferative retinopathy, however, laser treatment reduces retinal blood flow [14,19,27,28]. This may reflect either a reduced oxygen demand by the coagulated tissue, or an increase of oxygen diffusion from the choroid to the inner retina, or both [37].…”
Section: Introductionmentioning
confidence: 95%
“…The results, however, have been somewhat contradictory: Compared to healthy control groups, elevated [17,18,28,36], reduced [4][5][6], or unchanged [13,15,16,20] flow values were found in diabetics with no or non-proliferative retinopathy. In proliferative retinopathy, however, laser treatment reduces retinal blood flow [14,19,27,28]. This may reflect either a reduced oxygen demand by the coagulated tissue, or an increase of oxygen diffusion from the choroid to the inner retina, or both [37].…”
Section: Introductionmentioning
confidence: 95%
“…A corresponding decrease, as in retinal venular oxygen saturation, was observed in retinal venular diameter in the 'light' laser group (Group 1). Previous studies have shown that blood flow in the retinal vessels is reduced after PRP (Oswald et al 1985;Fujio et al 1994). The decrease in diameter in this group could indicate reduced blood flow as an expression of less oxygen demand by the tissue.…”
Section: Discussionmentioning
confidence: 54%
“…Dabei wurde bei Zentralvenenthrombosen an temporal oberen Qua dranten und bei .Astvenenthrombose im be troffenen Netzhautquadranten gemessen. Die bereits veröffentlichten Ergebnisse lassen zusammengefasst folgende Schlussfolgerun gen zu [Vilser et al, 1985] …”
Section: Fotokoagulation Bei Venösen Verschlusserkrankungenunclassified
“…dass bisher trotz guter Beispiele die the rapeutische Wirksamkeit der Folokoagulalion bei venösen Verschlusscrkrankungcn kli nisch nicht eindeutig nachgewiesen werden kann. Zum Einfluss der Fotokoagulation auf die Strömungsverhältnisse der Netzhaut bei venösen Verschlusserkrankungen gibt es nur wenige klinisch-experimentelle Untersu chungen mit direkten Durchblutungsmessun gen [Brandt et al, 1981;Vilser et al 1985], abgesehen von indirekten aus dem klinischen Bild abgeleiteten Hinweisen auf Veränderun gen der Netzhautdurchblutung. Ebenso un klar wie bei der diabetischen Retinopathie ist auch bei venösen Verschlusscrkrankungcn der therapeutische Wirkmechanismus der Fotokoagulation.…”
unclassified